Rayleigh/Raman lidar observations of gravity wave activity from 15 to 70 km altitude over Syowa (69°S, 40°E), the Antarctic - Kogure, Masaru; Nakamura, Takuji; Ejiri, Mitsumu K.; Nishiyama, Takanori; Tomikawa, Yoshihiro; Tsutsumi, Masaki; Suzuki, Hidehiko; Tsuda, Takuo T.; Kawahara, Takuya D.; Abo, Makoto (Journal of Geophysical Research: Atmospheres, 2017)
The potential energy of gravity waves (GWs) per unit mass (Ep), at altitudes of 15–70 km, has been examined from temperature profiles obtained by a Rayleigh/Raman lidar at Syowa Station (69°S, 40°E) from May 2011 to October 2013, with the exception of the summer months. The GWs with ground-based wave periods longer than 2 h and vertical wavelengths between 1.8 and 16 km were extracted from the temperature profiles. Ep was larger in winter than in spring and fall, although in 2012, at altitudes below 30 km, Ep was larger in spring than in winter and fall. Ep increased with a mean scale height of 11.3 km. Ep profiles showed a local maximum at an altitude of 20 km and a minimum at 25 km in almost every month, which has not been reported by previous studies observed by radiosondes. The values of Ep in October of 2012 were smaller at 35–60 km and larger at 20–35 km than those in October of 2011 and 2013. This difference in the Ep profile is most probably caused by different seasonal variations of zonal winds. The larger and smaller Ep values seem to be observed both below and above the altitude at which the zonal wind speed reached 0 m s−1. This result suggests that wind filtering of gravity waves with small phase speeds is significantly important in early spring. journal article